2020
DOI: 10.1002/adma.202001200
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Structure and Metamagnetic Transitions in the van der Waals Antiferromagnet CrPS4

Abstract: In 2D magnets, interlayer exchange coupling is generally weak due to the van der Waals layered structure but it still plays a vital role in stabilizing the long‐range magnetic ordering and determining the magnetic properties. Using complementary neutron diffraction, magnetic, and torque measurements, the complete magnetic phase diagram of CrPS4 crystals is determined. CrPS4 shows an antiferromagnetic ground state (A‐type) formed by out‐of‐plane ferromagnetic monolayers with interlayer antiferromagnetic couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 44 publications
5
86
0
Order By: Relevance
“…Having found the occurrence of band gap crossover in CrPS 4 , we then investigated the possible magnetic transformation under pressure as derived from the DFT + U (U = 2 eV) calculations. At ambient pressure, we found that the A-type AFM structure is the most energetically favorable state, consistent with previous DFT studies 40 and recent neutron diffraction experiments 35 . Our calculations suggest that the A-type AFM structure remains stable and no signs of change in the magnetic state is predicted to occur under pressure up to 20 GPa (see Supplementary Fig.…”
Section: Electronic Structures Of Crps 4 At High Pressuresupporting
confidence: 92%
See 2 more Smart Citations
“…Having found the occurrence of band gap crossover in CrPS 4 , we then investigated the possible magnetic transformation under pressure as derived from the DFT + U (U = 2 eV) calculations. At ambient pressure, we found that the A-type AFM structure is the most energetically favorable state, consistent with previous DFT studies 40 and recent neutron diffraction experiments 35 . Our calculations suggest that the A-type AFM structure remains stable and no signs of change in the magnetic state is predicted to occur under pressure up to 20 GPa (see Supplementary Fig.…”
Section: Electronic Structures Of Crps 4 At High Pressuresupporting
confidence: 92%
“…Among the 2D vdW magnetic materials, CrPS 4 is currently enjoying a surge of interest [30][31][32][33][34][35] . CrPS 4 was first synthesized in the 1970s and found to possess a monoclinic symmetry (C2/m space group) 36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first experimental observation of intrinsic ferromagnetism in monolayer CrI 3 1 and bilayer Cr 2 Ge 2 Te 6 2 , van der Waals (vdW) magnetic materials have attracted extensive attention in both fundamental research and practical applications [3][4][5][6][7][8][9] . The field of two-dimensional (2D) magnetic materials grows rapidly and various types of 2D magnetic materials have been discovered and synthesized, such as ferromagnetic (FM) magnets including Cr 2 Ge 2 Te 6 2 , CrBr 3 10 , Fe 3 GeTe 2 11,12 , Fe 5 GeTe 2 13 , monolayer VSe 2 14 , etc., and antiferromagnetic (AFM) magnets including CrCl 3 15 , transition metal phosphorous trichalcogenides MPX 3 (M = Mn, Fe, Ni; X = S, Se) [16][17][18][19] , CrPS 4 20 , MnBi 2 Te 4 21 , etc. The distinct spin-dependent properties of these materials provide a promising platform for the discovery and study of new quantum phenomena and design of novel spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[34] In our previous study, the low-field metamagnetic transition of CrPS 4 was identified as a spin-flop transition. [31] During the spin-flop transition, magnetic moments realign from the ac plane (at a small angle from the c axis) to the quasi-1D chains of CrS 6 octahedra along the b axis, showing both in-plane and out-of-plane magnetic anisotropy in CrPS 4 . Strong in-plane optical anisotropy has also been observed in CrPS 4 flakes, [33] confirming the inherent anisotropy of CrPS 4 .…”
Section: Introductionmentioning
confidence: 99%